Gestión documental de la empresa Asolimbrige de la ciudad de Babahoyo - Orellana Cedeño, Gisset Eugenia (2022)
File management within any organization is of vital importance to evidence relevant information. therefore, the workers of the companies are responsible for the proper handling of the documents, organizing and storing them respectively in accordance with the norms and criteria established by Law 594 of 2000. "General Law of Archives", The archiving process is achieved Organized, classified, labeled and numbered in folders and boxes the documents according to the TRD (Document Retention Tables) identifying the series, with their corresponding documentary types, the time of permanence in each stage of the life cycle and the importance in terms of time of conservation and preservation. A chronological order is obtained for an efficient search of the information required by the entity and at the same time documents that are not useful are purged, thus freeing up physical space so as not to increase unnecessary paper in the house destined for filing. Document management in companies is an inherent need in business activity, regardless of its size or the economic sector in which it participates. Document management is one of the areas of business activity in which the growing volume of information and documentation that companies are forced to process can seriously affect their business figures if not managed properly.